LIVED EXPERIENCES OF EJK VICTIM’S FAMILIES: AN INTERPRETATIVE PHENOMENOLOGICAL STUDY - Sorila, Marie Gold; Centeno, Johanna Mae; Reyes, Nikka Marielle (PEOPLE: International Journal of Social Sciences, 2018)
This study utilized Interpretative Phenomenological Analysis (IPA) to understand the issue of extrajudicial killing (EJK) in relation to the families of the victims. It specifically aims to explore their lived experiences and the patterns of their meaning-making. From the data gathered through unstructured interviews and drawings of five participant families, three superordinate themes that centered on their journey towards being an incomplete family emerged: [1] experience of being aware of victim’s drug involvement and the process of disaffirming it [2] experience of emotional struggles and the process of seeking justice and [3] experience of the reality of loss and the process of living with it. In addition, four superordinate themes arose with respect to their reflections which were brought by the death of the victim: [1] Drugs are destructive to the family [2] Philippine society is in chaos [3] loss of sanctity of life and [4] God is the ultimate refuge. The results discussed in the light of Filipino concepts and theories suggest that integral to the family dynamic of victim’s families was the concept of kapwa and this played a role in their experience of the adverse effect of the killing and in their effort to rebuild their family.